2014
DOI: 10.5455/2349-3291.ijcp20140802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anterior chest wall myofascial release on thoracic expansion in children with spastic cerebral palsy

Abstract: INTRODUCTION Cerebral Palsy (CP) describes a group of disorders of the development of movement and posture, causing activity limitations that are attributed to non-progressive disturbances that occurred in developing fetal or infant brain. The motor disorders of cerebral palsy are often accompanied by disturbances of sensation, cognition, communication, perception and/or behavior and/or a seizure disorders. 1 Cerebral palsy is the most common cause of severe physical disability in childhood. 2 Although CP is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Chest measurements were taken at three levels at the axilla, 3 fingers below the xiphoid process, and subcostal region. The results of this study showed that the chest expansion increased significantly [10]. In our study, while MFR did not decrease spasticity, there were improvements of medial heel pressure distribution and active contact area while walking.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Chest measurements were taken at three levels at the axilla, 3 fingers below the xiphoid process, and subcostal region. The results of this study showed that the chest expansion increased significantly [10]. In our study, while MFR did not decrease spasticity, there were improvements of medial heel pressure distribution and active contact area while walking.…”
Section: Discussionsupporting
confidence: 42%
“…Previous studies carried out in children with spastic cerebral palsy implied that myofascial release was useful in the management of spasticity [4,10,19,29]. Kumar et al [19] investigated the effect of myofascial release on spastic muscles.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Its evaluation and intervention involves an integral view that necessarily includes the fascial system, because it is a neurotransmitter, piezoelectric and tensegrite interface, so physiotherapy plays a vital card in the interaction of the child with cerebral palsy when including the fascial system. 17,18 This is a pioneer study not only for involving the assessment and possible diagnosis of the fascia through ultrasound, but also because of its use in the pediatric population, since from our understanding there are no other studies about the evaluation of the TLF in the population pediatric.…”
Section: Discussionmentioning
confidence: 99%